KETIDAKADILAN GENDER DALAM NOVEL DRUPADI KARYA SENO GUMIRA AJIDARMA (GENDER INJUSTICE IN THE NOVEL DRUPADI BY SENO GUMIRA AJIDARMA - Tati Akhbaryah (Universitas Lambung Mangkurat, 2022)
AbstractGender Injustice in The Novel Drupadi by Seno Gumira Ajidarma. This study aims todescribe gender injustice in the Novel